Identification of a novel structure-specific endonuclease AziN that contributes to the repair of azinomycin B-mediated DNA interstrand crosslinks. Issue 2 (12th November 2019) - Chen, Xiaorong; Sun, Yuedi; Wang, Shan; Ying, Kun; Xiao, Le; Liu, Kai; Zuo, Xiuli; He, Jing
Abstract: DNA interstrand crosslinks (ICLs) induced by the highly genotoxic agent azinomycin B (AZB) can cause severe perturbation of DNA structure and even cell death. However, Streptomyces sahachiroi, the strain that produces AZB, seems almost impervious to this danger because of its diverse and distinctive self-protection machineries. Here, we report the identification of a novel endonuclease-like gene aziN that contributes to drug self-protection in S. sahachiroi . AziN expression conferred AZB resistance on native and heterologous host strains. The specific binding reaction between AziN and AZB was also verified in accordance with its homology to drug binding proteins, but no drug sequestering and deactivating effects could be detected. Intriguingly, due to the high affinity with the drug, AziN was discovered to exhibit specific recognition and binding capacity with AZB-mediated ICL structures, further inducing DNA strand breakage. Subsequent in vitro assays demonstrated the structure-specific endonuclease activity of AziN, which cuts both damaged strands at specific sites around AZB-ICLs. Unravelling the nuclease activity of AziN provides a good entrance point to illuminate the complex mechanisms of AZB-ICL repair.